Development of Stick Model Manipulative Learning Media to Improve Addition and Subtraction Skills with Regrouping in Elementary School Students - Kadek Yudista Witraguna; I Gede Nesa Wijaya (Sekolah Dasar: Kajian Teori dan Praktik Pendidikan, 2024)
This study aims to develop stick model manipulative learning media to enhance addition and subtraction skills among elementary school students using the ADDIE development model. The media was designed with acrylic material and tested with 30 grade III students and 2 teachers at SD Negeri 1 Kemenuh. The development process included needs analysis, design, physical construction, and validation by five experts. The implementation phase evaluated the media's effectiveness in teaching, assessed its practicality using teacher and student response questionnaires, and measured its effectiveness through addition and subtraction tests administered before and after using the media. The results indicate that the media is effective in improving addition and subtraction skills with regrouping, evidenced by an average pre-test score of 69.8 and a posttest score of 77.2 with a significance level of Sig. < 0.05. The media’s practicality was rated as “Good,” with average teacher and student response scores of 43 (86 percent) and 44,3 (88.6 percent), respectively. These findings suggest that the stick model manipulative media is well-received by both teachers and students and is effective in enhancing basic math learning, improving students' understanding and motivation.